Peran Majelis Pendidikan Daerah dalam Melibatkan Peran Masyarakat Meningkatkan Mutu Pendidikan di Bener Meriah - Farida, Lasma; Abdussyukur (LSM Catimore dan Sahabat Jl. Paya Ilang/Pertamina Desa Lemah Burbana, Takengon, Aceh Tengah 24552, 2024)
The community's role to improving the quality of education is still weak. MPD with supervisory duties must assist community participation through school committees. This study aims to analyze the management of the Regional Education Council (MPD) and the role of the community in improving the quality of education in Bener Meriah. This study uses a qualitative descriptive research method. Data collection techniques in the study include interviews, documents, and observations. The data analysis techniques used are data reduction, presentation, and verification. The results of this study show that MPD management involves the role of the community in improving the quality of education in Bener Meriah, which consists of planning, implementation, supervision, and evaluation management. The management of MPD in involving the community is going well, even though at the level of implementation and execution of activities by the committee is slow, because the function of MPD is limited to mentoring, not execution.